Shallow Aquifer Groundwater Facies At Multiple Landuse Sites In Manglayang Volcanic Area, Jatinangor And Surroundings, Indonesia - Bombom Rachmat Suganda; Wahyudi Yusuf; Mochamad Nursiyam Barkah; Cecep Yandri Sunarie; M. Sapari Dwi Hadian (UIR PRESS, 2021)
Manglayang Mountain is generally composed by old and young volcanic materials. Older rocks are located around the northern part of mountain peak, in medial and distal parts. In the southern and southeastern parts composed by relatively young volcanic rocks starting from the proximal, medial to distal. These geologic conditions produce diverse aquifer systems. These differences in land use environments contribute to water quality conditions in local shallow aquifers. The research is therefore carried out in order to the effect of difference in land use environments on groundwater facies by dividing the area based on each land use. Land use in the research area is dominated by allotment of agricultural land, settlement, and industry. The study was conducted from the medial area to distal to the southern part of Manglayang Mountain, administratively including Sukasari, Jatinangor, and Rancaekek districts. To observe the groundwater conditions in the aquifer from the study area, physical and chemical parameters were tested. Chemical parameter test results were plotted using piper diagrams and Durov diagrams as a method that can illustrate the condition of groundwater facies. Physical characteristics of groundwater may reflect groundwater interactions with rocks. Measurable TDS concentrations of 48 - 299 mg / L and measured EC 100 - 1020 μmhos / cm, show different interaction conditions between groundwater with rocks or have received different material subsidies. Similarly, the occurrence of temperatures that vary considerably between air and water indicates the distance of groundwater sources with various water bodies. The groundwater facies that developed in the research area are generally dominated by Ca, HCO3 in the agricultural land use area, Mg, HCO3 in the settlement area, and in some Cl-facing evolving places in the industrial land use zones. In addition, there are also indications of mixing of anions and cations in groundwater samples in all three land use areas. This indicates that there has been a change in groundwater characteristics in some areas of land use utilization in the research area